(untitled) (The Research of Medical Science Review, 2025)
Objective: Clinical manifestation and pattern of dengue cases admitted in tertiary care hospital, Karachi. Patients and methods: Prospective observational study was conducted in the Department of Pediatric, Civil Hospital, Karachi. Children who presented in OPD or Emergency with clinical symptoms suggestive of dengue fever and age between 1 years to 15 years were included in this study. Baseline and clinical variables were collected through a structured questionnaire to collect the data such as age, clinical manifestations, laboratory parameters, and outcome. Data was analyzed using SPSS version 26. Results: Of the 249 patients, 127 (51.0%) were females. The overall mean age was 11.18±4.87 years. The most common clinical manifestations were fever (n = 249, 100%), followed by headache (n = 188, 75.5%), and irritability (n = 136, 54.61%). Most of the patients with dengue fever recovered (n = 185, 74.29%) and did not require admission (n = 64, 25.70%). Patients with rashes (n = 41, 64.06%), joint pain (n = 36, 56.25%), bleeding from nose (n = 20, 31.25%), bleeding from gums (n = 15, 23.43%), patients who had bruises (n = 22, 34.75%), patients with difficulty of breathing (n = 5, 7.81%), patients with low systolic blood pressure (mean difference 12.26±3.71 mmHg), low platelets count (mean difference 56.03±21.5 x 103), and patients with raised alanine aminotransferase (mean difference 20.77±4.31 IU/l) had significantly higher chances of hospitalization, p value <0.05. Conclusion: Dengue fever is common among young females with most of the patients presented with fever, headache, and irritability. Factors such as bleeding, thrombocytopenia, raised ALT, and shortness of breath were associated with higher rates of hospitalization.